2017
DOI: 10.1017/s0007485317000797
|View full text |Cite
|
Sign up to set email alerts
|

Improving the artificial diet for adult of seven spotted ladybird beetleCoccinella septempunctataL. (Coleoptera: Coccinellidae) with orthogonal design

Abstract: In this study, an orthogonal array design with 16 factors at two levels (216) was performed to develop an artificial diet rearing the adults of seven spotted ladybird beetle Coccinella septempunctata. The parameters of weight gain and survival rate of adults, preoviposition period, fecundity and hatching rate of diet-fed adults were monitored. The 16 factors were included: pork liver, infant formula, sucrose, olive oil, yolk, corn oil, yeast powder, cholesterol, casein, casein hydrolysate, vitamin powder, 65% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…In large-scale insect propagation, feeding aphid diets in captivity is an expensive and time-consuming method (Bonte et al, 2010). Therefore, it is necessary to develop artificial diets that H. axyridis can be supplemented with, in order to achieve the low-cost and continuous expansion of this insect that will facilitate the effective control of pests (Cheng et al, 2018). In response to this problem, various artificial insect diets have been exploited and proposed (Cohen, 2001;Castane and Zapata, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In large-scale insect propagation, feeding aphid diets in captivity is an expensive and time-consuming method (Bonte et al, 2010). Therefore, it is necessary to develop artificial diets that H. axyridis can be supplemented with, in order to achieve the low-cost and continuous expansion of this insect that will facilitate the effective control of pests (Cheng et al, 2018). In response to this problem, various artificial insect diets have been exploited and proposed (Cohen, 2001;Castane and Zapata, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to the results reported by Cheng et al . (2018). All these phenomena showed that the four artificial feeds could not meet the growth and development needs of the larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in China used an orthogonal design and included 16 selected factors tested at two levels, which was carried out to improve the artificial diet of C. septempunctata adult, weight gain, and fecundity of adults reared on this diet were respectively 87.46% and 62.70% of those reared on Aphis craccivora (Cheng et al . 2018). However, these artificial feeds have certain adverse effects on emergence rate, oviposition rate, hatch rate, etc ., in ladybirds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One goal in mass insect rearing is to use cost-effective artificial diets. Cheng et al (2017) found that the artificial diet for adults was superior to any previously developed formulas and might thus have potential for improving the artificial diet used for the mass rearing of Chrysopa septempunctata . These studies reveal that nutrient addition is beneficial to the metabolism and optimization of the artificial diet and thus affects the physiology and reproduction of H. axyridis .…”
Section: Introductionmentioning
confidence: 95%